The Teacher's Role in Developing Student Social Attitudes - Sarwono, Arsita Yunia; Murtono, Murtono; Widianto, Eko (Universitas Pendidikan Ganesha, 2020)
Lack of social attitudes that students have will have an impact on students' unfavorable affective. This research aimed to analyze the role of teachers in developing students' social attitudes. This research was a qualitative research with a theoretical approach. The population in this study was all students of grade V at SD 2 Tenggeles, totaling 19 students. The data collection technique was carried out in 3 stages, namely observation, interview and documentation. The data analysis technique in this study used a variety of techniques (triangulation) and was carried out continuously to completion. The results of the analysis of students' social attitudes during the learning process found the findings of several aspects of social attitudes in students including honesty, discipline, responsibility, caring, polite and self-confidence. Social attitudes are observed through student activities in learning such as being honest in doing assignments independently and being responsible for assignments that have been given by the teacher which must be done in a timely manner. It can be concluded that the social attitude of students at SD 2 Tenggeles is fairly good. Thus, the role of the teacher in shaping students' social attitudes is very important to be applied in the daily life of students in the school, family, and community environment.